O terço cantado e o altar dos santos na reza de São Sebastião na Comunidade Quilombola Barra do Aroeira - Pinto, Ronalda Rodrigues (Universidade Federal do Tocantins, 2021)
The present work deals with the prayers of São Sebastião and the altar of the saints, according to cultural experiences in the quilombola community of Barra do Aroeira, municipality of Santa Tereza-TO. The objective is to discuss the contributions of this imaginary to a creative process in hybrid scene practices and to the maintenance of traditions in the community. The methodological path, inserted in the context of teacher education, is autobiographical and investigative, including bibliographic research, field research and a poetic exercise linked to local culture. Placing the prayer of São Sebastião and its contexts as a place of knowledge that can be appreciated, consulted and analyzed, the work contributes to the dialogue between ancestry and the teachings of the theater and, to the extent of the scope of the proposal, for the strengthening of actions in the direction of the National Curriculum Guidelines for the Education of Ethnic-Racial Relations and for the Teaching of Afro-Brazilian and African History and Culture.